Are improvements in convenience good enough for consumers to prefer new food processing technologies?. Issue 1 (17th July 2021) - Garrido, Dolores; Karina Gallardo, Rosa
Abstract: We use choice experiments to investigate heterogeneity in preferences for a refrigerated ready‐to‐heat meal with an extended shelf life and the processing technology (i.e., microwave‐assisted pasteurization) that provides that longevity. On average, an extra day of shelf life decreases the utility associated with purchasing and eating the meal. A segmentation analysis reveals the presence of convenience consumers, who are willing to pay a premium for a more convenient meal (with an extended shelf life), but the interaction effect of shelf life with technology reverts their willingness to pay for an extra day of shelf life, suggesting a negative reaction to the new technology. (EconLit Citations: Q13, Q16, Q19).